DO PROFITABILITY, SOLVENCY, LIQUIDITY, AND FIRM SIZE INFLUENCE ON MANAGER’S DYSFUNCTIONAL BEHAVIOR IN FINANCIAL REPORTING OF INDONESIA TRANSPORTATION COMPANIES? - Milda, Asep Ahmad Kurniawan; Lumbanraja, Christopher Pangeran Bisuk; Debora, Desi; Prawiraputra, Rafli Rakhmansyah; Effendy, Rendy Mohammad Pasca; Latif, Dini Verdania (CENTRAL ASIA AND THE CAUCASUS, 2022)
Financial statements are information on how a company is performing. In order for the company's performance to look good and attract investors, managers may perform dysfunctional behavior on financial statements. Factors that can trigger dysfunctional behavior are conditions of profitability, solvency, liquidity and firm size. Therefore, this study aims to determine whether the condition of the company can affect the manager’s dysfunctional behavior. The population in this study are transportation companies that "go public". The sample was determined based on a purposive technique consisting of 10 Indonesian transportation companies listed on the Indonesia Stock Exchange in the 2016-2020 period. Data testing is done by using logistic regression. The results showed that partially Profitability, Solvency, Liquidity, and Firm Size had no significant effect on managers' dysfunctional behavior.Managers of companies that have high or low profitability, solvency and liquidity perform (not perform) dysfunctional behavior. Likewise, managers of large and small companies both may engage in (not engage in) dysfunctional behavior. Therefore, investors need to be careful in investing.